SPIRITUAL VALUES IN BIOLOGICAL MATERIALS: PLANTS GROWTH AND DEVELOPMENT - lutfauziah, asmaul; Handriyan, Aris (Journal Intellectual Sufism Research (JISR), 2018)
Spiritual value is a value that reflects human relations with their God. The spiritual value contained in each Biology material is different. This value can be taught well when the teacher has understood the spiritual value contained in the subject being taught. The subject of "growth and development" is taught at all levels of education from junior high school to college. The purpose of this study is to examine deeply the spiritual value of Biology material, especially the subject of "plant growth and development". This research is a qualitative descriptive study. The data of this study were obtained from content analysis, namely analysis of Biology material, analysis of the Qur'anic arguments, and analysis in the perspective of Sufism. In this article, the growth and development process is limited to seed germination and fruit ripening. The results of this study include: a) someone's faith is like a seed, faith that is only on the tongue like a seed coat, but when faith is produced from personal experience in the form of a gift from Allah (haqqul yaqin and ainul yaqin) it will lead someone to the stage of ma'rifat (like oil contained in seeds). b) Plant buds can grow from parts of plants and from seeds as stated in QS. al-An'am verse 95 and 99. c) In QS. Al-An'am verse 99 also explained that humans are commanded to observe and think about the process of fruit growth and pay attention to the maturity of the fruit in order to increase their faith in Allah.